CRITICAL ANALYSIS OF SOCIOLOGICAL FACTORS IMPACTING HEALTHCARE DELIVERY IN EXPLORING SOCIAL DETERMINANTS OF HEALTH AND STRATEGIES FOR ADDRESSING INEQUITIES - MOHAMMED MESFER MAHDI, Mohammad Ojyansead al rizq, Mohammad YahyaAlhammam, Muhammad Hadi Muhammad Al-Baibaa, Mohammad Hamad Mahdi Al Saleem, Hussein Hadi Muhammad Al-Baibaa, Ali Mohammed Jaber AL Khatrah, (Chelonian Research Foundation, 2022)
This paper is designed to give a valuable look at the actual situations of societies in health care, discussing social determinants of health and methods of addressing health inequalities. A study of the impact of social factors on healing is discussed with a focus on socioeconomic status (SES), schooling access, race/ethnicity, and healthcare inequality. The work investigates the condition of healthcare accessibility, utilization, and quality, along with the disproportionate health outcomes of different populations and groups. Health equity strategies, policy interventions, community-based initiatives, and reforms in the healthcare system are part of the strategies outlined in the paper. The last part of the paper refers to the recommendations and strategies for tackling social factors in healthcare delivery to overcome health disparities and enhance population health outcomes. Keywords: socioeconomic factors, health infrastructure, social determinants of health, health inequalities, healthcare provision, healthcare management, health results, program interventions, community engagement activities, and health system changes.